Energy Consumption Analysis of 5G C-V2X Sensor Sharing for Tele-Operated Driving - Hanyoung Park; Yongjae Jang; Kanghyun Ko; Ji-Woong Choi (IEEE Access)
As autonomous driving technology advances, the demand for unmanned mobility applications continues to grow. However, due to the imperfections in current autonomous driving systems, incidents still occur, highlighting the challenges of full driverless services. Moreover, the computation of complex autonomous driving algorithms requires an on-board computing unit, which consumes a large amount of energy. To address these limitations, tele-operated driving (ToD) has emerged as a promising solution for enhancing autonomous intelligent transportation systems (ITS). By enabling remote entities, such as remote users or servers, to control vehicles and manage edge cases in autonomous driving, ToD combines the benefits of both unmanned mobility and human oversight. To support ToD service, a real-time sensor sharing system for vehicles is essential, and cellular vehicle-to-everything (C-V2X) communication is suitable for the required network connectivity. However, most research has not focused on high-volume data transmission, which is required for sensor sharing systems. Additionally, the energy consumption of C-V2X, which directly impacts the battery efficiency of electric vehicles (EVs) as an example, has not been thoroughly examined. In this paper, we propose an evaluation framework for energy consumption analysis of ToD. Based on this framework, we analyze the energy consumption of vehicle for sensor data transmission over 5G C-V2X under varying channel conditions and multi-user scenarios. We also investigate the extent to which using ToD is energy-saving compared to the energy consumption of an on-board high-performance computing unit. Our findings indicate that the uplink-based sensor sharing system is more energy-efficient than its sidelink-based counterpart. Additionally, sensor sharing for ToD can save more energy of the battery in the vehicle compared to relying on the high-performance on-board computing unit.